Developing Curriculum And Tasks For Teaching Reading - Wulandari, Ella (English Education Department, Universitas Islam Indonesia, 2012)
This paper is aimed at proposing a curriculum and task design for teaching reading to students of an English teacher training. The curriculum discusses the needs and context analysis, goals, objectives, beliefs, content organization, task design, learning assessment and evaluation of the course. While being skill-oriented on one hand, the curriculum works towards a more process or discourse-oriented design. This is done to cater for the needs to build students' reading skills, understanding of text's construction and positive attitudes towards reading as not merely a means of acquiring a full command in the target language but also a tool to access knowledge and advancement.Key words: reading, curriculum and task design